SOCIO-ECONOMIC ASPECTS OF COMPLIANCE WITH BUSINESS ETHICS OF COMPANIES - Bobojonova Zarnigor Shokirovna; Khurramov Shahboz (Scholars Digest Publishing, 2024)
This article is devoted to the impact of activities carried out on the basis of the rules and principles of business ethics on the economic and social efficiency of the enterprise and the benefits of compliance with them.
Keywords: business ethics, code management, compliance management, social foundations of ethics.